Extensive margins of imports in The Great Import Recovery in Germany, 2009/2010 - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2013)
This paper contributes to the literature by documenting for the first time the contribution of adding (and dropping) goods and countries of origin to the sharp increase in imports of goods in the German economy as a whole during the Great Import Recovery in 2009/2010. The empirical investigation finds that firms that imported in both 2009 and 2010 are much more important for the import dynamics than import starters and import stoppers. Firms that increased their imports (and that were the drivers of the import boom) imported on average more goods and from more countries of origin in 2009 than firms that decreased their imports, and they increased both extensive margins of imports on average while firms with decreased imports reduced both the number of goods exported and the number of countries of origin.
Keywords: F14; 330; Extensive margins of imports; The Great Import Recovery; Germany